2012
DOI: 10.4049/jimmunol.1201383
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica YadA Mediates Complement Evasion by Recruitment and Inactivation of C3 Products

Abstract: Yersinia adhesin A (YadA) is a major virulence factor of Yersinia enterocolitica. YadA mediates host cell binding and autoaggregation and protects the pathogen from killing by the complement system. Previous studies demonstrated that YadA is the most important single factor mediating serum resistance of Y. enterocolitica, presumably by binding C4b binding protein (C4BP) and factor H, which are both complement inhibitors. Factor H acts as a cofactor for factor I-mediated cleavage of C3b into the inactive form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Despite this general downregulation, the overall expression levels, as indicated by the FPKM values, remain relatively high throughout the course of infection, regardless of the cellular location. The other downregulated gene, yadA, plays a vital role in adherence to host cell surfaces and prevention of complement-mediated inactivation (67,68), functions that have less importance once internalized. One striking observation about the pYV genes upregulated in response to internalization is that half of them have no known function.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this general downregulation, the overall expression levels, as indicated by the FPKM values, remain relatively high throughout the course of infection, regardless of the cellular location. The other downregulated gene, yadA, plays a vital role in adherence to host cell surfaces and prevention of complement-mediated inactivation (67,68), functions that have less importance once internalized. One striking observation about the pYV genes upregulated in response to internalization is that half of them have no known function.…”
Section: Resultsmentioning
confidence: 99%
“…1 b). Factor H has been shown to interact with several discontinuous stretches within the stalk domain of YadA [20][21][22]58] . Our data corroborate previous findings that the binding of factor H by Yersinia strains relies on the presence of YadA, but in contrast to Vn, there is no significant difference in binding efficiency in the various serotypes tested.…”
Section: Ye O:9 E40 Efficiently Binds Vnmentioning
confidence: 99%
“…Recently, we demonstrated a novel mechanism that contributes to serum resistance in Ye O:8 WA-314, and amended the current model of direct factor H binding to YadA 0: 3 and YadA 0: 9 . We have shown that Ye binds C3b or iC3b and thereby attracts high amounts of factor H to the bacterial surface [21] . This is different from the direct binding of factor H, which was shown earlier [19,20,22] .…”
mentioning
confidence: 99%
“…It was observed that an exchange of the YadA membrane anchor domain with that of Hia, EibA, or UspA1 from other gammaproteobacteria leads to comparable surface expression of such chimeric YadA proteins in Y. enterocolitica whereas virulence of these chimeric-protein-expressing strains was reduced for unclear reasons compared to wild-type YadA-expressing Y. enterocolitica (20). Accordingly, the exact locus of YadA mediating complement resistance of Y. enterocolitica by C3b and subsequent factor H binding could not be assigned in a recent study (33).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, recombinant BadA HN23 hybrid 3 expression did not confer complement resistance when bacteria were exposed to human serum for 2 h (data not shown). Although complement resistance has been excluded for B. henselae in a previous publication (46), it is well known that TAAs (such as YadA [33,47] or UspA [48]) confer serum resistance. From this, we conclude at least that the membrane anchor of YadA and truncated and hererologously expressed BadA do not contribute to serum resistance.…”
Section: Discussionmentioning
confidence: 99%